DISCRIMINATIVE POWER OF THE MODIFIED BONFERRONI’S TEST UNDER GENERAL AND PARTIAL NULL HYPOTHESIS - Conagin, Armando (REVISTA DE AGRICULTURA, 2015)
DISCRIMINATIVE POWER OF THE MODIFIED BONFERRONI’S TEST UNDER GENERAL AND PARTIAL NULL HYPOTHESIS